Inovação em tempos de pandemia: um estudo de dois casos no interior de São Paulo - Oliveira, Gustavo Domigues Ayres (Universidade Federal de São Carlos, 2021)
During the year of 2020, the business scenario was strongly hit by the Coronavirus pandemic, in this context of social and economic uncertainty, many companies try to reinvent themselves seeking competitiveness, or even, just surviving in their markets. Therefore, a very fertile soil to cultivate innovation is created. This article’s aims is to come up with an analysis of the innovation capability of two traditional companies over the pandemic context. To analyze its innovation capabilities adaptations to the methodologies made by the researched authors were crafted and applied in those companies, being a qualitive research with exploratory and descriptive character. The object of this research were two companies located at the southern region of Sao Paulo’s State, inserted in very traditional markets. The data was gathered through interviews with the company owners. The analyzed companies have presented a few innovations during the pandemic, showing different applications strategies to its technologies. The analysis has reached different technological capability levels for each firm, one presenting a low level of innovation capability, whilst the other has presented a intermediate level o innovation capability.
Innovation in pandemic times: a study in two cases of São Paulo inner
Keywords: Inovação; Capacidade de Inovação; Pandemia; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS